Positive active material for lithium secondary battery and method for preparing the same
Patent Information
- Application Number
- CN202610421225.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-11-28
- Filing Date
- 2026-04-01
- Publication Date
- 2026-10-16
AI Technical Summary
根据本发明的示例性的实施方案的正极活性物质包括多个一次颗粒聚集而成的团聚体形式的类单晶结构,因此可以有效地提高功率特性、长期耐久性和寿命特性。
Smart Images

Figure CN122930897A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a positive electrode active material for lithium secondary batteries and its preparation method. Background Technology
[0002] Rechargeable batteries are batteries that can be recharged and discharged repeatedly. With the development of the information communication and display industries, rechargeable batteries are widely used as power sources for portable electronic communication devices such as portable cameras, mobile phones, and laptops. In addition, in recent years, battery packs that include rechargeable batteries have been developed for use as power sources for environmentally friendly vehicles such as electric vehicles.
[0003] Secondary batteries can be categorized into, for example, lithium secondary batteries, nickel-cadmium batteries, and nickel-metal hydride batteries. Among them, lithium secondary batteries have high operating voltage and energy density per unit weight, and are advantageous for charging speed and lightweight design, so they are actively being researched and developed.
[0004] For example, NCM-based active materials containing nickel, cobalt, and manganese are being used as positive electrode active materials in lithium-ion batteries. As NCM-based active materials, examples include mid-Ni and high-Ni NCM-based active materials. Furthermore, as the application of lithium-ion batteries expands to large devices such as electric vehicles, there is a need to develop positive electrodes with improved electrochemical performance. Summary of the Invention
[0005] (a) Technical problems to be solved One technical problem of the present invention is to provide a positive electrode active material for lithium secondary batteries with improved electrochemical and lifetime characteristics.
[0006] One technical problem of the present invention is to provide a method for preparing the positive electrode active material for the lithium secondary battery.
[0007] (II) Technical Solution According to an exemplary embodiment, the positive electrode active material for a lithium secondary battery comprises a lithium-nickel metal oxide having a secondary particle shape formed by the aggregation of primary particles, wherein the number of primary particles contained within the secondary particles is 20 to 200, and wherein the number of primary particles having a long axis length of 0.8 μm or more is 20 to 80.
[0008] In an exemplary embodiment, the number of primary particles contained within the secondary particles can be 80 to 200.
[0009] In an exemplary embodiment, the number of primary particles with a major axis length of 0.8 μm or more can be 30 to 80.
[0010] In an exemplary embodiment, the relative standard deviation (%RSD) of the long axis of primary particles with a long axis length of 0.8 μm or more can be less than 35.
[0011] In an exemplary embodiment, the relative standard deviation (%RSD) of the maximum width of primary particles with a major axis length of 0.8 μm or more can be less than 40.
[0012] In an exemplary embodiment, the number of primary particles with a major axis length of 1.0 μm or more can be 20 to 50.
[0013] In an exemplary embodiment, the relative standard deviation (%RSD) of the long axis of primary particles with a long axis length of 1.0 μm or more can be less than 35.
[0014] In an exemplary embodiment, the relative standard deviation (%RSD) of the maximum width of primary particles with a major axis length of 1.0 μm or more can be less than 40.
[0015] In an exemplary embodiment, the average particle size (D50) of the primary particles can be from 0.8 μm to 3 μm.
[0016] In an exemplary embodiment, the lithium-nickel metal oxide may further comprise at least one element selected from W, Mo, Nb, B, Ta, and Sn.
[0017] In an exemplary embodiment, the span of the secondary particles, as represented by the following Formula 1, can be less than 0.9.
[0018] [Formula 1] Span = (D90 - D10) / D50 In Equation 1, D10 can be the particle size corresponding to a cumulative proportion of 10% in the volumetric cumulative particle size distribution of secondary particles, D90 can be the particle size corresponding to a cumulative proportion of 90% in the volumetric cumulative particle size distribution of secondary particles, and D50 can be the particle size corresponding to a cumulative proportion of 50% in the volumetric cumulative particle size distribution of secondary particles.
[0019] In an exemplary embodiment, the circularity of the secondary particles, as expressed by the following Formula 2, can be 0.70 or higher.
[0020] [Equation 2] In Equation 2, A can be the cross-sectional area of the secondary particle, and P can be the length of the particle boundary line.
[0021] In an exemplary embodiment, the roundness of the secondary particles, as represented by the following Formula 3, can be 0.90 or higher.
[0022] [Formula 3] In Equation 3, A can be the cross-sectional area of the secondary particle, and L can be the length of the major axis of the secondary particle.
[0023] A lithium secondary battery according to an exemplary embodiment may include: a positive electrode comprising the aforementioned positive electrode active material; and a negative electrode disposed opposite to the positive electrode.
[0024] (III) Beneficial Effects According to an exemplary embodiment of the present invention, the positive electrode active material comprises a quasi-single crystal structure in the form of aggregates formed by the aggregation of multiple primary particles, thereby effectively improving power characteristics, long-term durability and lifetime characteristics.
[0025] The primary particles of the positive electrode active material according to an exemplary embodiment of the present invention have uniform particle size, and therefore can have improved electrochemical properties.
[0026] Lithium-ion batteries incorporating the positive electrode active material of this invention can be widely used in green technology fields such as electric vehicles, battery charging stations, solar power generation, and wind power generation. Furthermore, lithium-ion batteries incorporating the positive electrode active material of this invention can be used in eco-friendly electric vehicles and hybrid vehicles, which prevent climate change by suppressing air pollution and greenhouse gas emissions. Attached Figure Description
[0027] Figure 1 This is a flowchart illustrating a method for preparing a positive electrode active material for a lithium secondary battery according to an exemplary embodiment.
[0028] Figure 2 and Figure 3 These are schematic plan views and schematic cross-sectional views of a lithium secondary battery according to an exemplary embodiment.
[0029] Figures 4a to 13c The images shown are scanning electron microscope (SEM) images (magnification: ×10000) of the primary particles of the positive electrode active material in the examples and comparative examples, respectively.
[0030] Figures 14a to 23bThese are scanning electron microscope (SEM) images of secondary particles of the positive electrode active material in the examples and comparative examples, respectively. Figures 14a to 23b In the image, a is a low-magnification image (magnification: ×1000), and b is a high-magnification image (magnification: ×10000).
[0031] Figures 24a to 33c The images shown are scanning electron microscope (SEM) images (magnification: ×5000) of the secondary particles of the positive electrode active material of the examples and comparative examples, respectively, and a diagram schematically showing the shape of the secondary particles of the positive electrode active material of each example and comparative example.
[0032] Explanation of reference numerals in the attached figures: 100: Positive electrode; 105: Positive electrode current collector 107: Positive electrode lead; 110: Positive electrode active material layer 120: Negative electrode active material layer; 125: Negative electrode current collector 127: Negative lead; 130: Negative electrode 140: Diaphragm; 150: Electrode assembly 160: Casing Detailed Implementation
[0033] The present invention provides a positive electrode active material for lithium secondary batteries (hereinafter referred to as "positive electrode active material") according to an exemplary embodiment.
[0034] According to an exemplary embodiment of the present invention, the positive electrode active material can have a shape that is an intermediate stage between polycrystalline and single crystal, i.e., a quasi-single crystal structure in the form of an aggregate of multiple primary particles (hereinafter, it can be simply referred to as "quasi-single crystal"). For example, according to an exemplary embodiment of the present invention, the positive electrode active material can have the following form: a small number of single crystal primary particles with relatively large diameters aggregate to form secondary particles.
[0035] Therefore, compared with the case where the positive electrode active material has a single crystal structure (hereinafter referred to as "single crystal"), the resistance of the positive electrode active material can be reduced, and compared with the case where the positive electrode active material has a polycrystalline structure (hereinafter referred to as "polycrystalline"), the side reactions between the positive electrode active material and the electrolyte and the generation of internal cracks can be prevented, thereby improving long-term durability and lifespan characteristics.
[0036] In an exemplary embodiment, the number of primary particles (hereinafter referred to as "primary particles") of positive electrode active material contained within secondary particles (hereinafter referred to as "secondary particles") of positive electrode active material having a quasi-monocrystalline structure can be 20 or more, 25 or more, 30 or more, 35 or more, 40 or more, 45 or more, 50 or more, 55 or more, 60 or more, 65 or more, 70 or more, 75 or more, 80 or more, 85 or more, 90 or more, 95 or more, or 100 or more. Within the above ranges, the resistance of the quasi-monocrystalline structure positive electrode active material is lower than that of the ordinary single-crystal structure positive electrode active material, thereby improving the power characteristics of the lithium secondary battery.
[0037] In an exemplary embodiment, the number of primary particles contained within the secondary particles can be less than 200, 195, 190, 185, 180, 175, 170, 165, 160, 155, 150, 145, 140, 135, 130, 125, or 120. Within the above range, compared to ordinary polycrystalline positive electrode active materials, quasi-monocrystalline positive electrode active materials can effectively prevent side reactions with the electrolyte and the generation of internal cracks in long-term evaluation.
[0038] In an exemplary embodiment, the number of primary particles contained within the secondary particles can be 20 to 200, 25 to 200, 30 to 200, 35 to 200, 40 to 200, 45 to 200, 50 to 200, 60 to 200, 70 to 200, or 80 to 200. Within the above range, compared to ordinary polycrystalline positive electrode active materials, quasi-monocrystalline positive electrode active materials can effectively prevent side reactions with the electrolyte and the generation of internal cracks in long-term evaluation. Furthermore, because the resistance of quasi-monocrystalline positive electrode active materials is lower than that of ordinary monocrystalline positive electrode active materials, the power characteristics of the lithium secondary battery can be improved.
[0039] In an exemplary embodiment, the primary particles may have a uniform size.
[0040] In an exemplary implementation, the size of the primary particles can be controlled within a certain range, and the relative standard deviation (%RSD) of the major axis and / or maximum width can be controlled within a certain range.
[0041] In an exemplary embodiment, the average particle size (D50) of the primary particles can be 0.8 μm or more, 0.81 μm or more, 0.82 μm or more, 0.83 μm or more, 0.84 μm or more, 0.85 μm or more, 0.86 μm or more, 0.87 μm or more, 0.88 μm or more, 0.89 μm or more, 0.9 μm or more, 0.91 μm or more, 0.92 μm or more, 0.93 μm or more, 0.94 μm or more, 0.95 μm or more, 0.96 μm or more, 0.97 μm or more, 0.98 μm or more, 0.99 μm or more, or 1.0 μm or more. Within the above range, compared with ordinary polycrystalline positive electrode active materials, quasi-monocrystalline positive electrode active materials can effectively prevent side reactions with electrolyte and the generation of internal cracks in long-term evaluation.
[0042] In an exemplary embodiment, the average particle size (D50) of the primary particles can be less than 3 μm, less than 2.9 μm, less than 2.8 μm, less than 2.7 μm, less than 2.6 μm, less than 2.5 μm, less than 2.4 μm, less than 2.3 μm, less than 2.2 μm, less than 2.1 μm, or less than 2.0 μm. Within the above range, the resistivity of the near-monocrystalline structure positive electrode active material is lower than that of the ordinary monocrystalline structure positive electrode active material, thereby improving the power characteristics of the lithium secondary battery.
[0043] In an exemplary embodiment, the average particle size (D50) of the primary particles can be 0.8 μm to 3 μm, 0.8 μm to 2.9 μm, 0.8 μm to 2.8 μm, 0.8 μm to 2.7 μm, 0.8 μm to 2.6 μm, 0.8 μm to 2.5 μm, 0.8 μm to 2.4 μm, 0.8 μm to 2.3 μm, 0.8 μm to 2.2 μm, 0.8 μm to 2.1 μm, or 0.8 μm to 2.0 μm. Within the above ranges, compared with ordinary polycrystalline positive electrode active materials, quasi-monocrystalline positive electrode active materials can effectively prevent side reactions with the electrolyte and the generation of internal cracks in long-term evaluation. Furthermore, since the resistance of quasi-monocrystalline positive electrode active materials is lower than that of ordinary monocrystalline positive electrode active materials, the power characteristics of the lithium secondary battery can be improved.
[0044] The average particle size (D50) of primary particles can be the particle diameter corresponding to 50% of the cumulative proportion of the volumetric particle size distribution of primary particles.
[0045] In one embodiment, the number of primary particles with a long axis length of 0.8 μm or more within the secondary particles can be 20 or more, 21 or more, 22 or more, 23 or more, 24 or more, 25 or more, 26 or more, 27 or more, 28 or more, 29 or more, 30 or more, 31 or more, or 32 or more. Within the above range, compared with ordinary polycrystalline positive electrode active materials, quasi-single-crystal positive electrode active materials can effectively prevent side reactions with the electrolyte and the generation of internal cracks in long-term evaluation.
[0046] Within the secondary particles, the number of primary particles with a long axis length of 0.8 μm or more can be less than 100, 99, 98, 97, 96, 95, 94, 93, 92, 91, 90, 89, 88, 87, 86, 85, 84, 83, 82, 81, 80, 79, 78, 77, 76, 75, 74, 73, 72, 71, 70, 69, 68, 67, 66, 65, 64, 63, 62, 61, or 60. Within the above range, the resistivity of the near-single-crystal structure positive electrode active material is lower than that of the ordinary single-crystal structure positive electrode active material, thereby improving the power characteristics of the lithium secondary battery.
[0047] Within the secondary particles, the number of primary particles with a long axis length of 0.8 μm or more can be 20 to 100, 20 to 90, 20 to 80, or 30 to 80. Within these ranges, compared to ordinary polycrystalline positive electrode active materials, quasi-monocrystalline positive electrode active materials can effectively prevent side reactions with the electrolyte and the formation of internal cracks in long-term evaluation. Furthermore, because the resistance of quasi-monocrystalline positive electrode active materials is lower than that of ordinary monocrystalline positive electrode active materials, the power characteristics of lithium-ion secondary batteries can be improved.
[0048] Within the secondary particles, the relative standard deviation (%RSD) of the long axis of primary particles with a long axis length of 0.8 μm or more can be below 35, 34, 33, 32, 31, 30, 29, 28, 27, 26, or 25. Within these ranges, compared to ordinary polycrystalline positive electrode active materials, quasi-monocrystalline positive electrode active materials can effectively prevent side reactions with the electrolyte and the formation of internal cracks in long-term evaluation. Furthermore, because the resistance of quasi-monocrystalline positive electrode active materials is lower than that of ordinary monocrystalline positive electrode active materials, the power characteristics of lithium secondary batteries can be improved.
[0049] Within the secondary particles, the relative standard deviation (%RSD) of the maximum width of primary particles with a long axis length of 0.8 μm or more can be below 40, 39, 38, 37, 36, 35, 34, 33, 32, 31, 30, 29, 28, 27, 26, or 25. Within the above range, compared with ordinary polycrystalline positive electrode active materials, quasi-monocrystalline positive electrode active materials can effectively prevent side reactions with the electrolyte and the generation of internal cracks in long-term evaluation. Furthermore, because the resistance of quasi-monocrystalline positive electrode active materials is lower than that of ordinary monocrystalline positive electrode active materials, the power characteristics of lithium secondary batteries can be improved.
[0050] In one embodiment, the number of primary particles with a long axis length of 1.0 μm or more within the secondary particles can be 20 or more, 21 or more, 22 or more, 23 or more, 24 or more, 25 or more, 26 or more, 27 or more, 28 or more, 29 or more, 30 or more, 31 or more, 32 or more, 33 or more, 34 or more, or 35 or more. Within the above range, compared with ordinary polycrystalline positive electrode active materials, quasi-single-crystal positive electrode active materials can effectively prevent side reactions with the electrolyte and the generation of internal cracks in long-term evaluation.
[0051] In one embodiment, the number of primary particles with a long axis length of 1.0 μm or more within the secondary particles can be 60 or less, 59 or less, 58 or less, 57 or less, 56 or less, 55 or less, 54 or less, 53 or less, 52 or less, 51 or less, 50 or less, 49 or less, 48 or less, 47 or less, 46 or less, or 45 or less. Within the above range, the resistance of the near-monocrystalline structure positive electrode active material is lower than that of the ordinary monocrystalline structure positive electrode active material, thereby improving the power characteristics of the lithium secondary battery.
[0052] In one embodiment, the number of primary particles with a long axis length of 1.0 μm or more within the secondary particles can be 20 to 60, 20 to 55, or 20 to 50. Within the above range, compared with ordinary polycrystalline positive electrode active materials, quasi-monocrystalline positive electrode active materials can effectively prevent side reactions with the electrolyte and the generation of internal cracks in long-term evaluation. At the same time, since the resistance of quasi-monocrystalline positive electrode active materials is lower than that of ordinary monocrystalline positive electrode active materials, the power characteristics of lithium secondary batteries can be improved.
[0053] Within the secondary particles, the relative standard deviation (%RSD) of the long axis of primary particles with a long axis length of 1.0 μm or more can be below 35, 34, 33, 32, 31, 30, 29, 28, 27, 26, 25, 24, 23, 22, 21, or 20. Within the above range, compared with ordinary polycrystalline positive electrode active materials, quasi-monocrystalline positive electrode active materials can effectively prevent side reactions with the electrolyte and the generation of internal cracks in long-term evaluation. Furthermore, because the resistance of quasi-monocrystalline positive electrode active materials is lower than that of ordinary monocrystalline positive electrode active materials, the power characteristics of lithium secondary batteries can be improved.
[0054] Within the secondary particles, the relative standard deviation (%RSD) of the maximum width of primary particles with a long axis length of 1.0 μm or more can be below 40, 39, 38, 37, 36, 35, 34, 33, 32, 31, 30, 29, 28, 27, 26, 25, 24, 23, 22, 21, or 20. Within the above range, compared with ordinary polycrystalline positive electrode active materials, quasi-monocrystalline positive electrode active materials can effectively prevent side reactions with the electrolyte and the generation of internal cracks in long-term evaluation. Furthermore, because the resistance of quasi-monocrystalline positive electrode active materials is lower than that of ordinary monocrystalline positive electrode active materials, the power characteristics of lithium secondary batteries can be improved.
[0055] The major axis of a primary particle can be the longest straight line passing through the cross-section of the primary particle, and the maximum width of the primary particle can be the longest straight line perpendicular to the major axis.
[0056] According to the exemplary embodiments, the span of the secondary particles can be less than 0.9, less than 0.89, less than 0.88, less than 0.87, less than 0.86, less than 0.85, less than 0.84, less than 0.83, less than 0.82, less than 0.81, less than 0.8, less than 0.79, less than 0.78, less than 0.77, less than 0.76, less than 0.75, less than 0.74, less than 0.73, less than 0.72, less than 0.71, or less than 0.7. Within the above range, compared with ordinary polycrystalline positive electrode active materials, quasi-monocrystalline positive electrode active materials can effectively prevent side reactions with electrolyte and the generation of internal cracks in long-term evaluation. At the same time, since the resistance of quasi-monocrystalline positive electrode active materials is lower than that of ordinary monocrystalline positive electrode active materials, the power characteristics of lithium secondary batteries can be improved.
[0057] The span of the secondary particles according to the exemplary embodiment can be 0.55 or more, 0.56 or more, 0.57 or more, 0.58 or more, 0.59 or more, 0.60 or more, 0.61 or more, 0.62 or more, 0.63 or more, 0.64 or more, or 0.65 or more. The span of the secondary particles according to the exemplary embodiment can be from 0.55 to 0.9 or from 0.57 to 0.88.
[0058] In an exemplary embodiment, the span of the secondary particles of the positive electrode active material can be represented by the following formula 1.
[0059] [Formula 1] Span = (D90 - D10) / D50 In Equation 1, D10 can be the particle size corresponding to a cumulative proportion of 10% in the volumetric cumulative particle size distribution of secondary particles, D90 can be the particle size corresponding to a cumulative proportion of 90% in the volumetric cumulative particle size distribution of secondary particles, and D50 can be the particle size corresponding to a cumulative proportion of 50% in the volumetric cumulative particle size distribution of secondary particles.
[0060] In an exemplary embodiment, the secondary particles may have a D10 of 5 μm to 8 μm, a D50 of 7 μm to 13 μm, and a D90 of 11 μm to 14.5 μm.
[0061] In one embodiment, the D50 of the secondary particles can be 7 μm or more, 7.2 μm or more, 7.5 μm or more, 7.8 μm or more, 8.0 μm or more, 8.2 μm or more, 8.5 μm or more, 8.8 μm or more, or 9.0 μm or more. In another embodiment, the D50 of the secondary particles can be less than 13.0 μm, less than 12.8 μm, less than 12.5 μm, less than 12.3 μm, less than 12.0 μm, less than 11.8 μm, less than 11.5 μm, less than 11.3 μm, less than 11.0 μm, less than 10.8 μm, or less than 10.5 μm.
[0062] The roundness of the secondary particles according to the exemplary embodiments can be 0.70 or higher, 0.71 or higher, 0.72 or higher, 0.73 or higher, 0.74 or higher, 0.75 or higher, 0.76 or higher, 0.77 or higher, 0.78 or higher, 0.79 or higher, or 0.80 or higher. Within the above ranges, the secondary particles can maintain a spherical shape without breaking.
[0063] The roundness of the secondary particles according to the exemplary embodiment can be 0.90 or higher, 0.91 or higher, 0.92 or higher, 0.93 or higher, 0.94 or higher, 0.95 or higher, 0.96 or higher, 0.97 or higher, or 0.98 or higher. Within the above range, the secondary particles can maintain a spherical shape without breaking.
[0064] In an exemplary embodiment, roundness can be represented by the following formula 2.
[0065] [Equation 2] In Equation 2, A can be the cross-sectional area of the secondary particle, and P can be the length of the particle boundary line.
[0066] For example, the cross-sectional area of a secondary particle can be the cross-sectional area of the particle shape obtained from an image of the secondary particle taken using a scanning electron microscope (SEM). Similarly, the particle boundary line can be the outer contour line of the shape obtained from an image of the secondary particle taken using a scanning electron microscope (SEM).
[0067] In an exemplary embodiment, roundness can be represented by the following formula 3.
[0068] [Formula 3] In Equation 3, A can be the cross-sectional area of the secondary particle, and L can be the length of the major axis of the secondary particle.
[0069] For example, the cross-sectional area of a secondary particle can be the cross-sectional area of the particle shape obtained from an image of the secondary particle taken using a scanning electron microscope (SEM). Similarly, the length of the major axis of a secondary particle can be the length of the major axis measured from the shape obtained from an image of the secondary particle taken using a scanning electron microscope (SEM).
[0070] In an exemplary embodiment, the positive electrode active material may contain a compound that enables reversible insertion and extraction of lithium ions.
[0071] According to an exemplary embodiment, the positive electrode active material may comprise a lithium-nickel metal oxide. The lithium-nickel metal oxide may further comprise at least one of cobalt (Co), manganese (Mn), and aluminum (Al).
[0072] In some embodiments, the positive electrode active material or the lithium-nickel metal oxide may include a layered structure or a crystal structure represented by the following chemical formula 1.
[0073] [Chemical Formula 1] Li x Ni a M b O2+z In chemical formula 1, the values can be 0.88≤x≤1.2, 0.6≤a≤0.99, 0.01≤b≤0.4, and -0.5≤z≤0.1. As mentioned above, M can contain Co, Mn, and / or Al.
[0074] The chemical structure represented by Formula 1 indicates the bonding relationships contained in the layered or crystalline structure of the positive electrode active material, and does not exclude other additional elements. For example, M may contain Co and / or Mn, and Co and / or Mn may be provided together with Ni as the main active element of the positive electrode active material. Formula 1 is provided to represent the bonding relationships of the main active elements and should be understood as including the introduction and substitution of additional elements.
[0075] In one embodiment, in addition to the primary active element, auxiliary elements may be further included to enhance the chemical stability of the positive electrode active material or the layered / crystal structure. These auxiliary elements may be incorporated into the layered / crystal structure and form bonds; this should be understood to also include the chemical structures represented by Formula 1.
[0076] The auxiliary element may include at least one of, for example, Na, Mg, Ca, Y, Ti, Hf, V, Nb, Ta, Cr, Mo, W, Fe, Cu, Ag, Zn, B, Al, Ga, C, Si, Sn, Ra, or P. The auxiliary element may function as an auxiliary active element, together with Co or Mn, to contribute to the capacity / power activity of the positive electrode active material; for example, Al.
[0077] For example, the positive electrode active material or the lithium-nickel metal oxide may include a layered structure or a crystal structure represented by the following chemical formula 1-1.
[0078] [Chemical Formula 1-1] Li x Ni a M1 b1 M2 b2 O 2+z In chemical formula 1-1, M1 may contain Co, Mn, and / or Al. M2 may contain the aforementioned auxiliary elements. In chemical formula 1-1, the following conditions may be met: 0.88≤x≤1.2, 0.6≤a≤0.99, 0.01≤b1+b2≤0.4, -0.5≤z≤0.1.
[0079] The positive electrode active material may further include coating elements or dopants. For example, elements that are substantially the same as or similar to the auxiliary elements described above can be used as coating elements or dopants. For example, one or more combinations of the elements described above can be used as coating elements or dopants.
[0080] Specifically, as the dopant, one or more of the elements such as W, Mo, Nb, B, Ta, and Sn can be used.
[0081] In one embodiment, elements such as Sr, Zr, La, and Ba may not be used as the dopant. Therefore, more uniform growth can be promoted while suppressing excessive growth of primary particles of the positive electrode active material.
[0082] For example, relative to the total molar number of Ni, M1, and M2, the content of the dopant can be 0.05 mol% or more, 0.06 mol% or more, 0.07 mol% or more, 0.08 mol% or more, 0.09 mol% or more, 0.1 mol% or more, or 0.15 mol% or more. Within the above ranges, uniform growth of primary particles can be promoted.
[0083] For example, relative to the total molar number of Ni, M1, and M2, the content of the dopant can be less than 1 mol%, less than 0.95 mol%, less than 0.9 mol%, less than 0.85 mol%, less than 0.8 mol%, less than 0.75 mol%, less than 0.7 mol%, less than 0.65 mol%, less than 0.6 mol%, less than 0.55 mol%, or less than 0.5 mol%. Within the above ranges, the degradation of the electrochemical performance of the secondary battery can be prevented.
[0084] For example, relative to the total molar number of Ni, M1, and M2, the content of the dopant can be 0.05 mol% to 1 mol%, 0.1 mol% to 0.8 mol%, 0.12 mol% to 0.6 mol%, or 0.15 mol% to 0.5 mol%. For example, in chemical formula 1-1, it can be 0.0005 ≤ b2 ≤ 0.01, 0.001 ≤ b2 ≤ 0.008, 0.0012 ≤ b2 ≤ 0.006, or 0.0015 ≤ b2 ≤ 0.005. Within the above ranges, the degradation of the electrochemical performance of the secondary battery can be prevented, while promoting the uniform growth of primary particles.
[0085] The coating element or dopant may be present on the surface of the lithium-nickel metal oxide particles, or may penetrate through the surface of the lithium-nickel metal oxide particles and be contained in the bonding structure represented by chemical formula 1 or chemical formula 1-1.
[0086] The positive electrode active material may comprise nickel-cobalt-manganese (NCM)-based lithium oxide. In this case, NCM-based lithium oxide with increased nickel content can be used.
[0087] Ni can be provided as a transition metal relevant to the power and capacity of lithium secondary batteries.
[0088] For example, as NCM-based lithium oxides, medium-nickel NCM-based lithium oxides with a Ni content (e.g., the mole fraction of nickel in the total moles of nickel, cobalt, and manganese) of 0.6 or more and less than 0.8, and high-nickel NCM-based lithium oxides with a Ni content of 0.8 or more can be used.
[0089] By using NCM-based lithium oxide with the aforementioned Ni content as the positive electrode active material, the capacity characteristics of the positive electrode and the lithium secondary battery can be improved.
[0090] However, with increasing Ni content, the long-term storage stability and lifetime stability of the cathode or secondary battery may relatively decrease, and side reactions with the electrolyte may also increase. However, according to an exemplary embodiment, conductivity can be maintained by including Co, while lifetime stability and capacity retention characteristics can be improved by including Mn.
[0091] In the NCM-based lithium oxide, the Ni content (e.g., the mole fraction of nickel in the total moles of nickel, cobalt, and manganese) can be 0.6 or more, 0.7 or more, or 0.8 or more. In some embodiments, the Ni content can be 0.6 to 0.95, 0.7 to 0.95, 0.8 to 0.95, 0.82 to 0.95, 0.83 to 0.95, 0.84 to 0.95, 0.85 to 0.95, or 0.88 to 0.95.
[0092] In some embodiments, the positive electrode active material may also include lithium cobalt oxide-based active material, lithium manganese oxide-based active material, lithium nickel oxide-based active material, or lithium iron phosphate (LFP)-based active material (e.g., LiFePO4).
[0093] In some embodiments, the positive electrode active material may include, for example, a manganese-rich (Mn-rich) based active material having a chemical structure or crystal structure represented by Formula 2, a lithium-rich layered oxide (LLO) / over-lithiated oxide (OLO) based active material, or a cobalt-less based active material.
[0094] [Chemical Formula 2] p[Li₂MnO₃]·(1-p)[Li q JO2] In Chemical Formula 2, 0<p<1 and 0.9≤q≤1.2 may be satisfied, and J may include at least one element selected from Mn, Ni, Co, Fe, Cr, V, Cu, Zn, Ti, Al, Mg and B.
[0095] The above positive electrode active material for lithium secondary batteries can be prepared by adjusting calcination conditions (temperature, time, etc.), the type and / or content of dopants, and the like.
[0096] Hereinafter, exemplary embodiments of the method for preparing the above positive electrode active material for lithium secondary batteries are provided.
[0097] Figure 1 is a flowchart for illustrating the method for preparing a positive electrode active material for a lithium secondary battery according to an exemplary embodiment.
[0098] Referring to Figure 1 , the active material metal source may be reacted to prepare an active material precursor (for example, step S10). The active material metal source may include a manganese source and a nickel source. In one embodiment, the active material metal source may further include a cobalt source.
[0099] Examples of the nickel source may include nickel sulfate (NiSO₄), nickel hydroxide (Ni(OH)₂), nickel nitrate (Ni(NO₃)₂), nickel acetate (Ni(CH₃CO₂)₂), hydrates thereof, and the like. Examples of the manganese source may include manganese sulfate (MnSO₄), manganese hydroxide (Mn(OH)₂), manganese nitrate (Mn(NO₃)₂), manganese acetate (Mn(CH₃CO₂)₂), hydrates thereof, and the like. Examples of the cobalt source may include cobalt sulfate (CoSO₄), cobalt hydroxide (Co(OH)₂), cobalt nitrate (Co(NO₃)₂), cobalt carbonate (CoCO₃), hydrates thereof, and the like.
[0100] In one embodiment, as the nickel source, manganese source and cobalt source, nickel sulfate, manganese sulfate and cobalt sulfate may be used respectively.
[0101] According to an exemplary embodiment, the above active material metal sources may be mixed and reacted, for example, by a co-precipitation method to obtain an active material precursor. For example, the active material precursor may be in the form of nickel-manganese hydroxide or nickel-manganese-cobalt hydroxide.
[0102] In an exemplary embodiment, the average particle diameter (D50) of the active material precursor may be 5 μm to 16 μm, 6 μm to 15 μm, or 7 μm to 14 μm. Within the above range, the number of primary particles contained in the secondary particles can be maintained in an appropriate range, and cracks in the particles can be prevented at the same time.
[0103] To facilitate the coprecipitation reaction, a precipitant and / or a chelating agent may be used. The precipitant may include alkaline compounds such as sodium hydroxide (NaOH) or sodium carbonate (Na₂CO₃). The chelating agent may include, for example, ammonia or ammonium carbonate.
[0104] In some embodiments, the active material metal source and a source containing the aforementioned dopants (e.g., W, Mo, Nb, B, Ta, Sn, etc.) can be introduced simultaneously. By simultaneously introducing the dopant-containing source, uniform primary particle growth can be achieved. For example, the dopant-containing source can be WO3, MoO3, Nb2O5, H3BO3, Ta2O5, SnO2, etc.
[0105] In an exemplary embodiment, the amount of dopant added can be 0.01 mol% to 1 mol%, 0.03 mol% to 1 mol%, or 0.05 mol% to 1 mol%, relative to the total number of moles of the added active metal source and the dopant-containing source. Within the above range, the degradation of the electrochemical performance of the secondary battery can be prevented, while promoting the uniform growth of primary particles.
[0106] The active material precursor can be mixed with a lithium source to prepare a mixture (e.g., S20 process). In an exemplary embodiment, the active material precursor and the lithium source can be mixed using a dry high-speed mixer.
[0107] The lithium source may include, for example, lithium carbonate (Li₂CO₃), lithium nitrate (LiNO₃), lithium acetate (CH₃COOLi), lithium oxide (Li₂O), lithium hydroxide (LiOH), etc. These lithium sources may be used alone or in combination of two or more. In one embodiment, lithium hydroxide may be used as the lithium source.
[0108] In some implementations, the dopant-containing source can be mixed with a lithium source.
[0109] The mixture can be calcined to form primary active material particles (e.g., S30 process).
[0110] According to an embodiment of the present invention, the calcination can be carried out at temperatures above 900°C, 910°C, 920°C, 930°C, 940°C, 950°C, 960°C, or 970°C. Within the above ranges, sufficient growth of primary particles can be induced.
[0111] In an exemplary embodiment, the calcination can be carried out at temperatures below 1100°C, 1090°C, 1080°C, 1070°C, 1060°C, 1050°C, 1040°C, 1030°C, 1020°C, 1010°C, 1000°C, 990°C, or 980°C. Within these ranges, excessive generation of secondary particles can be prevented.
[0112] In one embodiment, the calcination can be carried out at temperatures ranging from 900°C to 1100°C, 910°C to 1080°C, 920°C to 1050°C, 930°C to 1030°C, 940°C to 1000°C, 950°C to 990°C, or 960°C to 980°C.
[0113] The calcination process allows for heat treatment of the mixture at sufficiently high temperatures, preventing excessive formation of secondary particles while inducing sufficient growth of primary particles, thereby forming primary active material particles with a near-single-crystal structure.
[0114] In an exemplary embodiment, the calcination can be a first calcination, and the primary active material particles can be further calcined a second time. For example, positive electrode active material particles can be formed without additional calcination. For example, the primary active material particles can be calcined a second time to form positive electrode active material particles. The second calcination can be carried out at a temperature lower than the first calcination (e.g., S40 process). By further performing the second calcination at a relatively low temperature, more uniform growth can be promoted while suppressing excessive growth of primary particles.
[0115] According to an exemplary embodiment, the second calcination can be carried out at a temperature below 850°C, below 840°C, below 830°C, below 820°C, below 810°C, or below 800°C. Within the above ranges, excessive particle growth can be effectively suppressed.
[0116] According to an exemplary embodiment, the second calcination can be carried out at a temperature above 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, or 780°C. Within the above range, crystal properties can be improved.
[0117] In some embodiments, the second calcination temperature can be 700°C to 850°C, 720°C to 840°C, 740°C to 830°C, 750°C to 820°C, or 760°C to 800°C.
[0118] Within the above temperature range, crystal properties can be improved, and excessive particle growth can be suppressed more effectively.
[0119] Compared to the first calcination, the second calcination can be carried out for a longer period of time. Therefore, it is possible to prevent excessive particle growth while allowing for more uniform particle growth.
[0120] In some embodiments, the first calcination can be carried out for a time of less than 12 hours. For example, the first calcination can be carried out for less than 10 hours, less than 8 hours, less than 6 hours, or less than 5 hours.
[0121] The second calcination can be carried out for more than 5 hours, for example, more than 6 hours, more than 7 hours, more than 8 hours, more than 9 hours, or more than 10 hours.
[0122] After the second calcination, the positive electrode active material particles can be naturally cooled to room temperature, and then crushed and graded.
[0123] According to some implementation schemes, after the second calcination, impurities such as LiOH and Li2CO3 remaining on the surface of the positive electrode active material particles can be removed by washing with water-based solvents or organic solvents. Therefore, the electrochemical characteristics and stability of the secondary battery can be improved.
[0124] Figure 2 and Figure 3 These are schematic plan views and schematic cross-sectional views illustrating a lithium secondary battery according to an exemplary embodiment. For example, Figure 3 It is along Figure 2 A cross-sectional view taken along the thickness direction of the I-I' line.
[0125] exist Figure 2 and Figure 3 For ease of illustration, an exemplary lithium secondary battery is provided; however, the lithium secondary battery of the present invention is not limited to this. Figure 2 and Figure 3 The structure shown in the figure.
[0126] Reference Figure 2 and Figure 3 The lithium secondary battery may include an electrode assembly 150, which includes a positive electrode 100 and a negative electrode 130. The electrode assembly 150 may further include a separator 140. The electrode assembly 150 may be formed by stacking multiple positive electrodes 100, multiple negative electrodes 130, and a separator 140 (displaced between the positive electrodes 100 and the negative electrodes 130). The electrode assembly 150 may be contained in a housing 160 and immersed in an electrolyte.
[0127] The positive electrode 100 may include a positive electrode current collector 105 and a positive electrode active material layer 110, the positive electrode active material layer 110 being formed on at least one side of the positive electrode current collector 105. In some embodiments, the positive electrode active material layer 110 may be formed on both sides (top and bottom) of the positive electrode current collector 105.
[0128] The positive electrode active material layer 110 may contain a positive electrode active material containing the above-mentioned lithium-nickel metal oxide.
[0129] For example, the positive electrode active material can be mixed with binders, conductive materials and / or dispersing materials in a solvent and stirred to prepare a positive electrode slurry. The positive electrode slurry can be coated on at least one side of the positive electrode current collector 105 and then dried and calendered to manufacture the positive electrode 100.
[0130] For example, the positive current collector 105 may include stainless steel, nickel, aluminum, titanium, or alloys thereof. The positive current collector may also include aluminum or stainless steel surface-treated with carbon, nickel, titanium, or silver. For example, the thickness of the positive current collector 105 may be from 10 μm to 50 μm.
[0131] The adhesive may include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-co-hexafluoropropylene copolymer (poly(vinylidene fluoride-co-hexafluoropropylene)), polyacrylonitrile, polymethyl methacrylate, nitrile rubber (NBR), polybutadiene rubber (BR), styrene-butadiene rubber (SBR), polyacrylic acid-based adhesives, and poly(3,4-ethylenedioxythiophene) (PEDOT)-based adhesives, etc. In some embodiments, the PVDF-based adhesive can be used as a positive electrode adhesive.
[0132] The conductive material may be added to enhance conductivity and / or the mobility of lithium ions or electrons. For example, non-limiting examples of the conductive material may include carbon-based conductive materials such as graphite, carbon black, acetylene black, Ketjen black, graphene, carbon nanotubes, vapor-grown carbon fiber (VGCF), and carbon fibers, and / or metal-based conductive materials including perovskite materials such as tin, tin oxide, titanium oxide, LaSrCoO3, and LaSrMnO3.
[0133] According to an exemplary embodiment, the density (electrode density or mixture density) of the positive electrode active material layer 110 can be 2.8 g / cm³ (cc) or more. In one embodiment, the density of the positive electrode active material layer 110 can be 3.0 g / cm³ or more. For example, the density of the positive electrode active material layer 110 can be from 3.0 g / cm³ to 4.0 g / cm³ or from 3.0 g / cm³ to 3.5 g / cm³.
[0134] Within the aforementioned density range, particle cracking can be prevented, and the improved mechanical properties of lithium-nickel metal oxide particles can be fully realized in the active material layer unit.
[0135] The negative electrode 130 may include a negative electrode current collector 125 and a negative electrode active material layer 120, the negative electrode active material layer 120 being formed on at least one side of the negative electrode current collector 125. The negative electrode active material layer 120 may contain a negative electrode active material.
[0136] Non-limiting examples of the negative electrode current collector 125 include copper foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper, and polymer substrates coated with conductive metals. The thickness of the negative electrode current collector 125 can be, for example, from 10 μm to 50 μm.
[0137] The negative electrode active material can be any material known in the art capable of adsorbing and desorbing lithium ions, without particular restriction. For example, the negative electrode active material can be carbon-based materials such as crystalline carbon, amorphous carbon, carbon composites, and carbon fibers, lithium metal, lithium alloys, silicon-containing materials, or tin-containing materials.
[0138] Examples of amorphous carbon include hard carbon, soft carbon, coke, mesocarbon microbeads (MCMB), and mesophase pitch-based carbon fiber (MPCF).
[0139] Examples of crystalline carbon include natural graphite, artificial graphite, graphitized coke, graphitized mesophase carbon microspheres (MCMB), graphitized mesophase pitch-based carbon fibers (MPCF), and other graphite-based carbons.
[0140] The lithium metal may include pure lithium metal or lithium metal with a protective layer formed to inhibit dendrite growth, etc. In one embodiment, the lithium-containing metal layer deposited or coated on the negative electrode current collector can be used as the negative electrode active material layer. In one embodiment, the lithium thin film layer can be used as the negative electrode active material layer.
[0141] Elements included in the lithium alloy may include aluminum, zinc, bismuth, cadmium, antimony, silicon, lead, tin, gallium, or indium.
[0142] The silicon-containing substance can provide further increased capacity characteristics. The silicon-containing substance may include Si, SiO x (0<x<2), metal-doped SiO x (0<x<2), silicon-carbon composites, and the like. The metal may include lithium and / or magnesium, and the metal-doped SiO x (0<x<2) may include metal silicates.
[0143] In some embodiments, the negative electrode active material may be mixed and stirred with a binder, a conductive material and / or a dispersion material, etc. in a solvent to prepare a negative electrode slurry. The negative electrode slurry may be applied to at least one side of the negative electrode current collector, followed by drying and rolling to fabricate the negative electrode 130.
[0144] The binder and the conductive material may use substances of substantially the same or similar types as the binder and the conductive material contained in the positive electrode. In some embodiments, the negative electrode binder may use styrene-butadiene rubber (SBR)-based binders, carboxymethyl cellulose (CMC), polyacrylic acid-based binders, polyethylenedioxythiophene (poly(3,4-ethylenedioxythiophene), PEDOT)-based binders, and the like.
[0145] In some embodiments, the separator 140 may be disposed between the positive electrode 100 and the negative electrode 130. The separator 140 may include a porous polymer film or a porous nonwoven fabric.
[0146] The porous polymer film may include polyolefin-based polymers such as ethylene polymers, propylene polymers, ethylene / butene copolymers, ethylene / hexene copolymers, and ethylene / methacrylate copolymers.
[0147] The porous nonwoven fabric may include high-melting-point glass fibers, polyethylene terephthalate fibers, and the like. The separator 140 may further include a ceramic-based material. For example, inorganic particles may be coated on the polymer film or dispersed in the polymer film to improve heat resistance.
[0148] According to an exemplary embodiment, the battery cell can be defined by a positive electrode 100, a negative electrode 130, and a separator 140, and can be formed, for example, by stacking multiple battery cells. The electrode assembly 150 can be of the winding type, stacking type, z-folding type, or stack-folding type.
[0149] The electrode assembly 150 can be housed together with the electrolyte within the housing 160, thereby defining a lithium secondary battery. According to an exemplary embodiment, a non-aqueous electrolyte can be used.
[0150] Non-aqueous electrolytes may contain a lithium salt as the electrolyte and an organic solvent, wherein the lithium salt may be, for example, Li... + X - This indicates that the anion (X) of the lithium salt is... - ), can be exemplified by F - Cl - ,Br - I - NO3 - N(CN)2 - BF4 - ClO4 - PF6 - (CF3)2PF4 - (CF3)3PF3 - (CF3)4PF2 - (CF3)5PF - (CF3)6P - CF3SO3 - CF3CF2SO3 - (CF3SO2)2N - (FSO2)2N - CF3CF2(CF3)2CO - (CF3SO2)2CH - (SF5)3C - (CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - CH3CO2 - SCN - (CF3CF2SO2)2N - wait.
[0151] The organic solvents may include, for example, propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), methyl propyl carbonate, dipropyl carbonate, dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, vinylene carbonate, sulfolane, γ-butyrolactone, propylene sulfite, tetrahydrofuran, etc. These may be used alone or in combination of two or more.
[0152] In some implementations, a solid electrolyte can be used instead of the non-aqueous electrolyte described above. In this case, the lithium secondary battery can be manufactured as an all-solid-state battery. Additionally, a solid electrolyte layer can be disposed between the positive and negative electrodes instead of the aforementioned separator.
[0153] The solid electrolyte may include a sulfide-based electrolyte. As a non-limiting example, the sulfide-based electrolyte may include Li₂S-P₂S₅, Li₂S-P₂S₅-LiCl, Li₂S-P₂S₅-LiBr, Li₂S-P₂S₅-LiCl-LiBr, Li₂S-P₂S₅-Li₂O, Li₂S-P₂S₅-Li₂O-LiI, Li₂S-SiS₂, Li₂S-SiS₂-LiI, Li₂S-SiS₂-LiBr, Li₂S-SiS₂-LiCl, Li₂S-SiS₂-B₂S₃-LiI, Li₂S-SiS₂-P₂S₅-LiI, Li₂S-B₂S₃, and Li₂S-P₂S₅-Z. m S n (m and n are positive numbers, Z is Ge, Zn, or Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li p MO q (p and q are positive numbers, M is P, Si, Ge, B, Al, Ga, or In), Li 7-x PS 6-x Cl x (0≤x≤2), Li 7-x PS 6-x Br x (0≤x≤2), Li 7-x PS 6-x I x (0≤x≤2), etc. These can be used individually or in combination of two or more.
[0154] In one embodiment, the solid electrolyte may also include oxide-based amorphous solid electrolytes such as Li2O-B2O3-P2O5, Li2O-SiO2, Li2O-B2O3, and Li2O-B2O3-ZnO.
[0155] like Figure 2 As shown, the tabs (positive tab and negative tab) can protrude from the positive current collector 105 and negative current collector 125 belonging to each cell and extend to one end of the housing 160. The tabs can be fused to said one end of the housing 160 and connected to electrode leads (positive lead 107 and negative lead 127) extending to or exposed outside the housing 160.
[0156] Figure 2 The diagram shows the positive electrode lead 107 and the negative electrode lead 127 protruding from the upper side of the housing 160 in a planar direction, but the position of the electrode leads is not limited thereto. For example, the electrode leads may protrude from at least one of the two sides of the housing 160, or from the lower side of the housing 160. Alternatively, the positive electrode lead 107 and the negative electrode lead 127 may be formed to protrude from different sides of the housing 160, respectively.
[0157] The lithium secondary battery can be manufactured in shapes such as cylindrical, prismatic, pouch, or coin, for example, using a can.
[0158] The following experimental examples, including embodiments and comparative examples, are presented to aid in understanding the present invention. However, these embodiments are only for illustrating the present invention and do not limit the scope of the claims. Various changes and modifications can be made to the embodiments within the scope of the present invention and the technical concept, which will be obvious to those skilled in the art. Such variations and modifications are naturally within the scope of the claims.
[0159] Examples and Comparative Examples (1) Example 1 1) Preparation of positive electrode active material NiSO4, CoSO4, and MnSO4 were added to distilled water in a ratio of 88:7:5 and mixed. The distilled water was then bubbled with N2 for 24 hours to remove dissolved oxygen before use.
[0160] The above mixed solution was then added to a reactor at 60°C, and NH4OH was added to the reactor. The mixture was then stirred at a constant rate to prepare a transition metal solution. NaOH was added to the reactor at a constant rate, such that the molar ratio of transition metal to NaOH in the transition metal solution was 1:2. A co-precipitation reaction was then carried out to obtain precursor particles of the active material in hydroxide form (D50: 10.22 μm). The average particle size (D50) of the obtained precursor particles was measured as the particle size corresponding to 50% of the cumulative volume in the volumetric particle size distribution obtained using laser diffraction (Microtrac, MT 3000).
[0161] The active material precursor particles, lithium hydroxide, and dopant-containing source WO3 (0.25 mol% of WO3 relative to the total number of moles of the active material precursor particles) are added to a dry high-speed mixer and then mixed uniformly for about 5 minutes to obtain a mixture.
[0162] The mixture is placed in a calcining furnace and heated to 970°C at a rate of 2°C / min, and held at 970°C for 5 hours to perform the first calcination.
[0163] Then, the temperature is lowered to 780°C and maintained at 780°C for 10 hours to carry out the second calcination.
[0164] During the calcination process, oxygen is continuously introduced into the calcination furnace at a flow rate of 10 mL / min. After calcination, the material is naturally cooled to room temperature, then pulverized and graded to obtain positive electrode active material particles.
[0165] 2) Manufacturing of secondary batteries (coin-shaped half-cells) The positive electrode active material particles, carbon black, and polyvinylidene fluoride (PVDF) are dispersed in N-methyl-2-pyrrolidone (NMP) at a weight ratio of 93:5:2 to prepare the positive electrode slurry.
[0166] The positive electrode slurry was coated onto an aluminum foil (thickness: 20 μm) and then dried and rolled to obtain the positive electrode. Lithium metal (thickness: 1.0 mm) was used as the counter electrode (negative electrode).
[0167] The positive and negative electrodes are cut into circular shapes with diameters of Φ14 and Φ16 respectively and stacked. A diaphragm (polyethylene (PE) with a thickness of 13µm) cut into Φ19 is placed between the positive and negative electrodes to form an electrode assembly.
[0168] The electrode assembly is housed in a coin-shaped battery casing (2032 specification), and an electrolyte is injected into the coin-shaped battery casing to obtain an initial battery.
[0169] The electrolyte used was a 1M LiPF6 solution prepared using EC / EMC (10:20 v / v) mixed solvent.
[0170] The initial lithium secondary battery was subjected to CC / CV charging (0.1C constant current, CC cut-off condition: 4.3V, CV cut-off condition: 0.005C) and CC discharging (0.1C constant current, 3.0V cut-off) at 25°C. This charging and discharging cycle was performed twice to obtain an activated lithium secondary battery.
[0171] (2) Examples 2 to 20 and Comparative Examples 1 to 11 The positive electrode active material and lithium secondary battery that meet the requirements of the examples and comparative examples in Table 1 below were manufactured by the same method as in Example 1, except that the Ni content of the precursor, the type / content of the dopant and the calcination temperature were adjusted.
[0172] [Table 1] Evaluation example (1) Measurement of the physical properties of the positive electrode active material 1) Primary particles The positive electrode active material particles of the examples and comparative examples were analyzed by scanning electron microscopy (SEM). The SEM instrument used was a Thermo Fisher Helios Nanolab 650.
[0173] Figures 4a to 13c The images shown are scanning electron microscope (SEM) images (magnification: ×10000) of the primary particles of the positive electrode active material of the examples and comparative examples, respectively.
[0174] Figures 4a to 4c This is a scanning electron microscope (SEM) image (magnification: ×10000) of the primary particles of the positive electrode active material of Example 1.
[0175] Figures 5a to 5c This is a scanning electron microscope (SEM) image (magnification: ×10000) of the primary particles of the positive electrode active material of Example 2.
[0176] Figures 6a to 6c This is a scanning electron microscope (SEM) image (magnification: ×10000) of the primary particles of the positive electrode active material of Example 3.
[0177] Figures 7a to 7c This is a scanning electron microscope (SEM) image (magnification: ×10000) of the primary particles of the positive electrode active material of Example 4.
[0178] Figures 8a to 8c This is a scanning electron microscope (SEM) image (magnification: ×10000) of the primary particles of the positive electrode active material of Example 5.
[0179] Figures 9a to 9c This is a scanning electron microscope (SEM) image (magnification: ×10000) of the primary particles of the positive electrode active material of Example 6.
[0180] Figures 10a to 10c This is a scanning electron microscope (SEM) image (magnification: ×10000) of the primary particles of the positive electrode active material of Comparative Example 1.
[0181] Figures 11a to 11c This is a scanning electron microscope (SEM) image (magnification: ×10000) of the primary particles of the positive electrode active material of Comparative Example 2.
[0182] Figures 12a to 12c This is a scanning electron microscope (SEM) image (magnification: ×10000) of the primary particles of the positive electrode active material of Comparative Example 3.
[0183] Figures 13a to 13c This is a scanning electron microscope (SEM) image (magnification: ×10000) of the primary particles of the positive electrode active material of Comparative Example 4.
[0184] SEM analysis was used to measure the number of primary particles contained within secondary particles, the number of primary particles with a major axis length greater than 0.8 μm, and the number of primary particles with a major axis length greater than 1.0 μm. Furthermore, the relative standard deviation (%RSD) of the major axis / maximum width for primary particles with a major axis length greater than 0.8 μm and the relative standard deviation (%RSD) of the major axis / maximum width for primary particles with a major axis length greater than 1.0 μm were measured.
[0185] The measurement results are shown in Table 2 below.
[0186] [Table 2] 2) Secondary particles Figures 14a to 23b These are scanning electron microscope (SEM) images of secondary particles of the positive electrode active material from the examples and comparative examples, respectively (magnification: at...). Figures 14a to 23b In the image, a is a low-magnification image (magnification: ×1000), and b is a high-magnification image (magnification: ×10000).
[0187] Figures 14a to 14b This is a scanning electron microscope (SEM) image of the secondary particles of the positive electrode active material in Example 1 (magnification: Figure 14a For low-magnification images (magnification: ×1000), Figure 14b For high-magnification images (magnification: ×10000)).
[0188] Figures 15a to 15b This is a scanning electron microscope (SEM) image of the secondary particles of the positive electrode active material in Example 2 (magnification: Figure 15a For low-magnification images (magnification: ×1000), Figure 15b For high-magnification images (magnification: ×10000)).
[0189] Figures 16a to 16b This is a scanning electron microscope (SEM) image of the secondary particles of the positive electrode active material in Example 3 (magnification: Figure 16a For low-magnification images (magnification: ×1000), Figure 16b For high-magnification images (magnification: ×10000)).
[0190] Figures 17a to 17b This is a scanning electron microscope (SEM) image of the secondary particles of the positive electrode active material in Example 4 (magnification: Figure 17a For low-magnification images (magnification: ×1000), Figure 17b For high-magnification images (magnification: ×10000)).
[0191] Figures 18a to 18b This is a scanning electron microscope (SEM) image of the secondary particles of the positive electrode active material in Example 5 (magnification: Figure 18a For low-magnification images (magnification: ×1000), Figure 18b For high-magnification images (magnification: ×10000)).
[0192] Figures 19a to 19b This is a scanning electron microscope (SEM) image of the secondary particles of the positive electrode active material in Example 6 (magnification: Figure 19a For low-magnification images (magnification: ×1000), Figure 19b For high-magnification images (magnification: ×10000)).
[0193] Figures 20a to 20b This is a scanning electron microscope (SEM) image of the secondary particles of the positive electrode active material of Comparative Example 1 (magnification: Figure 20a For low-magnification images (magnification: ×1000), Figure 20b For high-magnification images (magnification: ×10000)).
[0194] Figures 21a to 21bThis is a scanning electron microscope (SEM) image of the secondary particles of the positive electrode active material in Comparative Example 2 (magnification: Figure 21a For low-magnification images (magnification: ×1000), Figure 21b For high-magnification images (magnification: ×10000)).
[0195] Figures 22a to 22b This is a scanning electron microscope (SEM) image of the secondary particles of the positive electrode active material in Comparative Example 3 (magnification: Figure 22a For low-magnification images (magnification: ×1000), Figure 22b For high-magnification images (magnification: ×10000)).
[0196] Figures 23a to 23b This is a scanning electron microscope (SEM) image of the secondary particles of the positive electrode active material in Comparative Example 4 (magnification: Figure 23a For low-magnification images (magnification: ×1000), Figure 23b For high-magnification images (magnification: ×10000)).
[0197] Figures 24a to 33c The images shown are scanning electron microscope (SEM) images (magnification: ×5000) of the secondary particles of the positive electrode active material of the examples and comparative examples, respectively, and a diagram schematically showing the shape of the secondary particles of the positive electrode active material of each example and comparative example.
[0198] Figure 24a This is a scanning electron microscope (SEM) image (magnification: ×5000) of the secondary particles of the positive electrode active material in Example 1.
[0199] Figures 24b to 24c It is shown schematically. Figure 24a A diagram showing the shape of the secondary particles.
[0200] Figure 25a This is a scanning electron microscope (SEM) image (magnification: ×5000) of the secondary particles of the positive electrode active material in Example 2.
[0201] Figures 25b to 25c It is shown schematically. Figure 25a A diagram showing the shape of the secondary particles.
[0202] Figure 26a This is a scanning electron microscope (SEM) image (magnification: ×5000) of the secondary particles of the positive electrode active material in Example 3.
[0203] Figures 26b to 26c It is shown schematically. Figure 26a A diagram showing the shape of the secondary particles.
[0204] Figure 27aThis is a scanning electron microscope (SEM) image (magnification: ×5000) of the secondary particles of the positive electrode active material in Example 4.
[0205] Figures 27b to 27c It is shown schematically. Figure 27a A diagram showing the shape of the secondary particles.
[0206] Figure 28a This is a scanning electron microscope (SEM) image (magnification: ×5000) of the secondary particles of the positive electrode active material in Example 5.
[0207] Figures 28b to 28c It is shown schematically. Figure 28a A diagram showing the shape of the secondary particles.
[0208] Figure 29a This is a scanning electron microscope (SEM) image (magnification: ×5000) of the secondary particles of the positive electrode active material in Example 6.
[0209] Figures 29b to 29c It is shown schematically. Figure 29a A diagram showing the shape of the secondary particles.
[0210] Figure 30a This is a scanning electron microscope (SEM) image (magnification: ×5000) of the secondary particles of the positive electrode active material of Comparative Example 1.
[0211] Figures 30b to 30c It is shown schematically. Figure 30a A diagram showing the shape of the secondary particles.
[0212] Figure 31a This is a scanning electron microscope (SEM) image (magnification: ×5000) of the secondary particles of the positive electrode active material of Comparative Example 2.
[0213] Figures 31b to 31c It is shown schematically. Figure 31a A diagram showing the shape of the secondary particles.
[0214] Figure 32a This is a scanning electron microscope (SEM) image (magnification: ×5000) of the secondary particles of the positive electrode active material of Comparative Example 3.
[0215] Figures 32b to 32c It is shown schematically. Figure 32a A diagram showing the shape of the secondary particles.
[0216] Figure 33a This is a scanning electron microscope (SEM) image (magnification: ×5000) of the secondary particles of the positive electrode active material of Comparative Example 4.
[0217] Figures 33b to 33c It is shown schematically. Figure 33a A diagram showing the shape of the secondary particles.
[0218] Table 3 shows the particle size analysis (PSA) data, roundness, and sphericity of the secondary particles in the examples and comparative examples.
[0219] [Table 3] (2) Evaluation of coin-type half-cells 1) Discharge capacity (mAh / g) and charge / discharge efficiency (%) The coin-shaped half-cells of the examples and comparative examples were charged and discharged at 0.1C, and the initial charge capacity and initial discharge capacity were measured. Then, the charge / discharge efficiency was evaluated by calculating the percentage of the initial discharge capacity to the initial charge capacity.
[0220] Charge / discharge efficiency (%) = (Initial discharge capacity) / (Initial charge capacity) × 100% 2) Ratio characteristics (%) The coin-type half-cells of the examples and comparative examples were subjected to two CC / CV charging cycles (0.1C constant current, CC cutoff condition: 4.3V, CV cutoff condition: 0.005C) and CC discharging cycles (0.1C constant current, 3.0V cutoff), followed by one more CC / CV charging cycle (0.5C constant current, CC cutoff condition: 4.3V, CV cutoff condition: 0.005C) and CC discharging cycle (4.0C constant current, 3.0V cutoff). Rate characteristics were evaluated by converting the 4.0C discharge capacity to the 0.1C discharge capacity as a percentage (%).
[0221] Rate capability (%) = (4.0C discharge capacity) / (0.1C discharge capacity) × 100% 3) High-temperature (45℃) capacity retention rate (%) At 45°C, the coin-type half-cells of the examples and comparative examples were subjected to repeated CC / CV charging (0.5C constant current, CC cutoff condition: 4.3V, CV cutoff condition: 0.05C) and CC discharging (1.0C constant current, 3.0V cutoff) 150 times, and the discharge capacity was measured. The capacity retention was then evaluated by calculating the percentage of the discharge capacity at the 150th cycle to the initial discharge capacity measured in step 1).
[0222] Capacity retention rate (%) = (Discharge capacity at 150th discharge) / (Initial discharge capacity) × 100% The evaluation results are shown in Table 4 below.
[0223] [Table 4]
Claims
1. A positive electrode active material for lithium secondary batteries, said positive electrode active material comprising lithium-nickel metal oxide, said lithium-nickel metal oxide having a secondary particle shape formed by primary particle aggregation. in, The number of primary particles contained within the secondary particles is between 20 and 200. In the primary particles, the number of primary particles with a major axis length of 0.8 μm or more is 20 to 80.
2. The positive electrode active material for lithium secondary batteries according to claim 1, wherein, The number of primary particles contained within the secondary particles is between 80 and 200.
3. The positive electrode active material for lithium secondary batteries according to claim 1, wherein, In the primary particles, the number of primary particles with a major axis length of 0.8 μm or more is 30 to 80.
4. The positive electrode active material for lithium secondary batteries according to claim 1, wherein, The relative standard deviation (%RSD) of the long axis of primary particles with a long axis length of 0.8 μm or more is less than 35.
5. The positive electrode active material for lithium secondary batteries according to claim 1, wherein, The relative standard deviation (%RSD) of the maximum width of primary particles with a major axis length of 0.8 μm or more is less than 40.
6. The positive electrode active material for lithium secondary batteries according to claim 1, wherein, In the primary particles, the number of primary particles with a major axis length of 1.0 μm or more is 20 to 50.
7. The positive electrode active material for lithium secondary batteries according to claim 6, wherein, The relative standard deviation (%RSD) of the long axis of primary particles with a long axis length of 1.0 μm or more is less than 35.
8. The positive electrode active material for lithium secondary batteries according to claim 6, wherein, The relative standard deviation (%RSD) of the maximum width of primary particles with a major axis length of 1.0 μm or more is less than 40.
9. The positive electrode active material for lithium secondary batteries according to claim 1, wherein, The average particle size D50 of the primary particles is 0.8 μm to 3 μm.
10. The positive electrode active material for lithium secondary batteries according to claim 1, wherein, The lithium-nickel metal oxide further comprises at least one element selected from W, Mo, Nb, B, Ta, and Sn.
11. The positive electrode active material for lithium secondary batteries according to claim 1, wherein, The span of the secondary particles, as represented by Equation 1 below, is 0.9 or less. [Formula 1] Span = (D90 - D10) / D50 In Equation 1, D10 is the particle size corresponding to a cumulative proportion of 10% in the volumetric cumulative particle size distribution of secondary particles, D90 is the particle size corresponding to a cumulative proportion of 90% in the volumetric cumulative particle size distribution of secondary particles, and D50 is the particle size corresponding to a cumulative proportion of 50% in the volumetric cumulative particle size distribution of secondary particles.
12. The positive electrode active material for lithium secondary batteries according to claim 1, wherein, The roundness of the secondary particles, as expressed by the following formula 2, is 0.70 or higher. [Equation 2] , In Equation 2, A is the cross-sectional area of the secondary particle, and P is the length of the particle boundary line.
13. The positive electrode active material for lithium secondary batteries according to claim 1, wherein, The roundness of the secondary particles, as expressed by the following formula 3, is 0.90 or higher. [Formula 3] , In Equation 3, A is the cross-sectional area of the secondary particle, and L is the length of the major axis of the secondary particle.
14. A lithium secondary battery, comprising: The positive electrode comprises the positive electrode active material for lithium secondary batteries as described in claim 1; as well as The negative electrode is positioned opposite to the positive electrode.